Redistribuição e reconhecimento: o caso das políticas sociais nos municípios de Natal e Belo horizonte - Morais, Thais de Freitas (2010)
This research refers to a comparative study of social policies from the cities of Natal (RN) and Belo Horizonte (MG). Understanding that the demands for social justice in contemporary societies require both economic redistribution, and cultural recognition, we set out to investigate, according to Nancy Fraser s formulations (1996, 2005a, 2005b, 2007), how these two municipalities incorporate these dimensions in their social programs.